Implementasi Alat Monitoring Suhu Ruangan Berbasis Internet Of Things (IoT) Menggunakan Metode MQTT dan HTML Pada Ruangan Server Universitas Indo Global Mandiri Palembang - Parhan Oktaria Putra; Herri Setiawan; Zaid Romegar Mair (Informatics Engineering, Faculty of Computer Science, 2023)
The server room is an important room that is useful as a place to store devices related to the server. Inside the server room itself there are also important data that need to be protected so that security standards are needed to protect the room starting from air temperature, humidity, fire prevention. To meet these security standards, a tool is provided to monitor the temperature in the server room. By using a temperature sensor, namely DHT-11 and the NodeMCU ESP8266 Module as a tool for reading sensors, MQTT as a communication protocol and HTML for simple display, Telegram as a notification medium. This tool is useful so that we don't have to come directly to the server room to check room temperature and activities in checking temperature become easier because a website is provided that provides information about room temperature in real time